Potencialidades e limitações de uma proposta para o ensino de física no segundo grau: o caso do ensino do efeito fotoelétrico - Bataglia, Danilo Paulo (2019)
This work developed an active learning methodology to teach the concept of photoelectric effect that was applied in a class composed of students of the first, second and third years of high school, who were attending classes of physics in a private school in a city of the interior of the state of São Paulo. The classes lasted 50 minutes each and 7 classes were used. The activity began with the pre-test, then an activity was performed using the "Photoelectric Effect" Software available on the University of Colorado Boulder page, applied in the school's computer room. For this activity the students followed a script established by the researcher containing steps to be followed by the students to work with the simulation. During this stage the teacher circled the room to answers questions. After completing the steps the students answered the post-test and then the opinion questionnaire. To verify the learning, a quantitative analysis was performed at first, comparing the correct answers obtained by the students in the pre-test and in the post-test. The quantitative analysis was not enough to produce all the necessary information about the students' learning, so a qualitative analysis based on the answers of the tests applied was made, trying to understand in the best way all type of learning that occurred.Analyzing questions 1 and 2 of the post-test, which evaluated the concept of photoelectric effect and eletron work function, 5 of the 13 participants were able to develop the concept of photoelectric effect and 4 managed to develop the concept, but with some kind of error. About the concept of eletron work function, 4 students answered correctly and another 4 students answered the question with some kind of error. The other students responded in the wrong way, with responses more related to silicon than the eletron work function